Bahasa Inggris - Suardi, Ulil Maulana; Rifdan; Novayanti Sopia Rukmana; Abd. Rahman Yus (International Journal Of Public Policy and Bureaucracy, 2025)
Population administration is an integral part of public services that are important in maintaining the administrative order of the country and providing basic rights to citizens, such as the right to identity and access to other public services. In Indonesia, Population Administration is strictly regulated through various regulations to ensure the accuracy and validity of population data, as well as to provide easy access for citizens to obtain population documents such as identity cards (KTP), birth certificates, and other documents. The main regulations governing population administration include Law No. 23/2006 on Population Administration, which is then strengthened by various implementing regulations. This study aims to describe the strategy of improving population administration services at the Population and Civil Registration Office (Disdukcapil) of Bulukumba Regency. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis was carried out with the stages of data condensation, data presentation, and conclusion drawing and verification. The results showed that the strategy of improving population administration services at Disdukcapil Bulukumba Regency can be analyzed through five strategic variables, namely: (1) Plan, which has been well organized, can be seen from strategic planning which includes cooperation with sub-districts and the provision of services at the sub-district office to facilitate community access. (2) Ploy (tactic), which is shown by the application of digitalization to speed up the process of verifying population data and improve communication between employees, so that services become more efficient. (3) Pattern, which has been well coordinated through the implementation of services in accordance with Standard Operating Procedures (SOP), although there are still complaints related to injustice in services that prioritize relatives. (4) Position, which reflects Disdukcapil's efforts to position itself as an institution oriented towards community satisfaction by presenting digital-based service innovations. (5) Perspective, which still requires improvement, especially in improving fairness and certainty of service completion time, as highlighted by the community. Although there are several challenges in implementing the service strategy, Disdukcapil Bulukumba Regency continues to conduct periodic evaluations and utilize digital technology to increase the effectiveness of population administration services. With the right strategy, it is expected that services will be more efficient, transparent and responsive to community needs.